Changes in endogenous gene transcript and protein levels in maize plants expressing the soybean ferritin transgene - Kanobe, Milly N.; Rodermel, Steven R.; Bailey, Theodore; Scott, Paul (Frontiers in Plant Science, 2013)
Transgenic agricultural crops with increased nutritive value present prospects for contributing to public health. However, their acceptance is poor in many countries due to the perception that genetic modification may cause unintended effects on expression of native genes in the host plant. Here, we tested effects of soybean ferritin transgene (SoyFer1, M64337) on transcript and protein levels of endogenous genes in maize. Results showed that the transgene was successfully introduced and expressed in the maize seed endosperm. mRNA abundance of seven tested iron homeostasis genes and seed storage protein genes differed significantly between seed samples positive and negative for the transgene. The PCR negative samples had higher zein and total protein content compared to the positive samples. However, PCR positive samples had significantly higher concentrations of calcium, magnesium, and iron. We have shown that the soybean ferritin transgene affected the expression of native iron homeostasis genes in the maize plant. These results underscore the importance of taking a holistic approach to the evaluation of transgenic events in target plants, comparing the transgenic plant to the untransformed controls.